Flexible wire-shaped lithium-sulfur batteries with fibrous cathodes assembled via capillary action. (March 2017) - Liu, Ruiqing; Liu, Yuejiao; Chen, Jun; Kang, Qi; Wang, Linlin; Zhou, Weixin; Huang, Zhendong; Lin, Xiujing; Li, Yi; Li, Pan; Feng, Xiaomiao; Wu, Gang; et al.
Abstract: Wire-Shaped lithium sulfur batteries are regarded as a promising solution for burgeoning wearable electronics, intelligent textiles, flexible electronics, due to its great advantages of high theoretical specific capacity and energy density, flexibility and weavability. However, there remains a critical challenge in the manufacturing of mechanically robust, highly conductive and industrially processable fibrous cathodes. Here, a new and general strategy is proposed to produce freestanding sulfur-containing fibrous electrodes using industrially weavable stainless steel fibers (SSFs) as supports and current collectors. The SSFs based electrodes not only enable the feasibility of continuous processing and large-scale production, but also feature a porous fibrous structure that allows the imbibition of graphene-sulfur composite by facile capillary action. The wire-shaped lithium sulfur battery fabricated by this hybrid fibrous cathode shows mechanical robustness, high flexibility and excellent electrochemical performances. It can reach a capacity of 335 mAh g −1 at a current density of 167.5 (0.1 C) mA g −1, keep high stability after running for 100 cycles and realize a series of sophisticated applications for the flexible and wearable electronics. Graphical abstract: fx1 Highlights: The 316 L SSFs are creatively introduced to prepare fibrous Li-S batteries cathodes. The rGO/S composites can be self-assembled onto the metal yarns by capillary action. The Li-S battery shows excellent mechanical and electrochemical performances.